Britain's Empire Marketing Board and the failure of soft trade policy, 1926–33. (31st March 2021) - Higgins, David M; Varian, Brian D
Abstract: Before 1932, Britain's essentially free-trade policy left barely any scope for reciprocating the preferential tariffs that the Dominions applied to Britain's exports. Thus, Britain attempted to reciprocate by means of a "soft" trade policy aimed at increasing Britain's imports from the empire through wide-reaching publicity coordinated by the Empire Marketing Board (EMB). This article, the first econometric assessment of the EMB, argues that there was not a differential increase in the volume of those imports advertised by the EMB. Principal arguments for this failure are that British consumers were frequently unaware of the geographic origin of many commodities and that they tended to identify company brand more than country of origin.